How effective is autologous serum therapy in chronic autoimmune urticaria - Imran Majid; Shazia Shah; Altaf Hassan; Saima Aleem; Khalid Aziz (Wolters Kluwer Medknow Publications, 2015)
Background: Chronic autoimmune urticaria (CAU) is one of the most challenging therapeutic problems faced by a dermatologist. Recently, weekly autologous serum injections have been shown to induce a prolonged remission in this disease. Aim: To evaluate the efficacy of repeated autologous serum injections in patients with CAU. Materials and Methods: Seventy patients of CAU were prospectively analyzed for the efficacy of nine consecutive weekly autologous serum injections with a post-intervention follow-up of 12 weeks. Total urticaria severity score (TSS) was monitored at the baseline, at the end of treatment and lastly at the end of 12 weeks of follow up. Response to treatment was judged by the percentage reduction in baseline TSS at the end of treatment and again at the end of 12 weeks-follow-up. Results: Out of the 70 patients enrolled, 11 dropped out of the injection treatment after one or the first few doses only. Among the rest of 59 patients, only 7 patients (12%) went into a partial or complete remission and remained so over the follow-up period of 12 weeks. Forty patients (68%) did not demonstrate any significant reduction in TSS at the end of the treatment period. Rest of the 12 patients showed either a good or excellent response while on weekly injection treatment, but all of them relapsed over the follow-up period of 12 weeks. Conclusion: Autologous serum therapy does not seem to lead to any prolonged remission in patients of CAU.